Agricultural Changes in North-Western India as Influenced by Green Revolution and Irrigation Water Availability - Prasad, Rajendra; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2022)
North-western India is known as the ‘Granary of India’ after the introduction of wheat dwarf varieties in the mid-sixties. Dwarf gene varieties of wheat are highly responsive to inputs viz. fertilizer and irrigation water. Earlier in the Kharif season maize, pearl millet, minor millets and cotton were the predominant crops in north-western India i.e. Punjab, Haryana and Uttar Pradesh. However, with the increasing infrastructure for irrigation through canals, pump sets and tube wells, farmers started to grow rice even though Punjab soils are not suitable for rice production. Now, most of the farmers are growing rice in Kharif season and wheat in Rabi season. Hence, the rice-wheat cropping system has become dominant and is being practiced in nearly 10 million ha area. Farmers in north-western India also grow a lot of sugarcane crop, which produce huge tonnage but at the cost of luxury consumption of water. ‘Green Revolution’, which was a new chapter in the Agriculture history of India, started in this region, but it is using its water too lavishly surpassing its recharge. There is an urgent need to change or at least modify the ‘rice–wheat’ and sugarcane–wheat cropping systems (CS) of this region by less water-demanding ones viz. maize–wheat, cotton–wheat, soybean–wheat and pigeon pea–wheat etc. cropping systems. Even though, they may be less profitable but will ensure the sustainability of agriculture in this region in long-term.